In situ-mobilization of arsenic in groundwater: an innovative remediation approach? - Maier, Martin V.; Isenbeck-Schröter, Margot; Klose, Lukas; Ritter, Simon M.; Scholz, Christian (Procedia earth and planetary science, 2017)
In order to evaluate an inefficient pump & treat remediation at a contaminated site in Germany, processes of arsenic release into groundwater were studied. Groundwater and aquifer material sampling indicated elevated mobility of arsenic and a differentiated spatial distribution of As(V) and As(III). An artificial increase of arsenic mobilization in addition to the ongoing pump & treat remediation was supposed to be a suitable and sustainable remediation method for the contaminated site. Typically, arsenic mobility is increased under iron-reducing conditions, yet a number of water ingredients trigger arsenic mobility, e.g phosphate. The affinity of phosphate to sorb onto mineral phases leads to a competitive surface-complexation of phosphate and arsenic. In column tests, the release of arsenic from the contaminated aquifer material was significantly enhanced by the addition of phosphate. Under oxic and anoxic redox conditions the geochemical processes led to elevated release of mobile arsenic fractions up to a total of 50-60% and almost 100% in a period of 90 days, respectively. Eventually, the amendment of phosphate is able to enhance the efficiency of a pump & treat remediation and is currently investigated on field scale on-site.